DAMPAK ARUS LALU LINTAS TERHADAP TINGKAT LAYANAN JARINGAN JALAN KOTA KEDIRI BERDASARKAN IHCM 1997 - Cahyono, Andri Dwi; Mahardana, Zendy Bima; Hidiyati, Evita Fitrianis; Rahmawaty, Fitry (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The function of j alan is a means of passing goods and services which is one of the needs for society, nation, and state. According to the Director General of Highways, 2012 it is known that every economic growth of 1% has an impact on increasing traffic users by 1.5%. The increase in traffic in Kediri City has resulted in an increase in the movement of people and goods, where the movement activity clearly requires adequate transportation facilities and infrastructure both in quality and quantity. The method used with the IHCM 1997 method (Indonesia Highway Capacity Method 1997) uses field survey data in the form of traffic flow data, observation time, parking and general data on side obstacles. Meanwhile, the secondary data is in the form of geometric images of Panglima Sudirman road from the Kediri spatial and urban planning office. The study concluded that the level of road service is at level E which is a level with a moderate level of congestion, although it is still at a moderate level of congestion, but needs to be watched out for because the impact has been felt by road users. One of the alternatives used is to minimize disturbances on the left and right sides of the road, so that it is expected to be able to optimize the level of road service on the Sudirman road section.